Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Dengan Moderasi GCG - Henny Wirianata (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
The objective of this study is to obtain empirical evidence about the influence of capital structure, profitability, firm size, and good corporate governance (GCG) towards the firm value of manufacturing companies listed in the Indonesia Stock Exchange period 2016-2018. The data were tested in this research using EVIEWS 10. The results show that capital structure proxies by DER and profitability proxies by NPM have a positive and significant effect on firm value. Meanwhile, profitability proxies by ROA, firm size, and GCG proxies by institutional ownership have negative and significant effects on firm value. The results also show that institutional ownership could not moderate the effects of capital structure, profitability, and firm size towards the firm value of manufacturing companies listed in the Indonesia Stock Exchange period 2016-2018.